George S. Cook papers - Cook, George S. (George Smith), 1819-1902.; Cook, Huestis P. (Huestis Pratt), 1868-1951.
Business correspondence and account books (1845-1854, 1859-1864) from Cook's photographic studio in Charleston, S.C.; a biographical sketch of Cook written by his son, Huestis Cook, 1951; and an unidentified photograph. The account books (4 volumes) include references to Cook's photography in the South during the Civil War and to photographic processes used by Cook.
Photographer, of Charleston, S.C. (1849-1880), and Richmond, Va. (1880-1902).
Collection material in English.
Keywords: Commercial photography -- South Carolina -- Charleston; Photography -- Processing; United States -- History -- Civil War, 1861-1865 -- Photography; Photographers